If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11-46=5(x-2)-5
We move all terms to the left:
11-46-(5(x-2)-5)=0
We add all the numbers together, and all the variables
-(5(x-2)-5)-35=0
We calculate terms in parentheses: -(5(x-2)-5), so:We get rid of parentheses
5(x-2)-5
We multiply parentheses
5x-10-5
We add all the numbers together, and all the variables
5x-15
Back to the equation:
-(5x-15)
-5x+15-35=0
We add all the numbers together, and all the variables
-5x-20=0
We move all terms containing x to the left, all other terms to the right
-5x=20
x=20/-5
x=-4
| -4.4r=22 | | 2x+18-x=180 | | 9(k-6)-(8k+9)=3 | | 600=x+(1.5*x) | | 11-17z=5-20z | | 600=(600/x)+(1.5*x) | | -19f-9=-18f+15-7 | | 15.75=500×.5r | | 600=600/x+1.5*x | | 4/5x-3/4=3/10x-1 | | -18k-17=-k | | 36.4=2.8d | | f+4.6=4.7 | | 2d-10+9d=8+9d | | -n-10=5n+8 | | 1/4y+4=3/2 | | 2+8s=10+2s+10s | | 8x+78=2x+14 | | -1+5b=7+4b | | x^2−10x+22=0 | | -8r=-5r-6 | | 3(x+2)+5(x-7)=43 | | -3p-5=-8p-10 | | 3(x+2)=43 | | 68x+88=0 | | -4=4+s | | 1/4p=11 | | -5c-3=-4c | | -6n=66 | | (7x-5)/(3x+2)=9 | | -3d-5=2d | | 5s-2=4s |